The Power of Incumbency: Measuring Accountability and Advantage in Indonesia’s Legislative Elections - Yulistiani, Irma; Rezki, Jahen F. (UNIVED Press, 2026)
Elections serve as a primary mechanism of democratic accountability, allowing voters to reward effective representatives and remove underperformers. In Indonesia’s open-list proportional representation system, incumbency offers a tangible record for retrospective evaluation. Using candidate-level data from the 2019 and 2024 legislative elections and an Ordinary Least Squares linear probability model, this study finds that incumbents hold a decisive advantage: winning in 2019 increases the likelihood of winning in 2024 by 61.4 percentage points. These results indicate that voters strongly value demonstrated performance over partisan loyalty, reinforcing incumbency as a channel for political accountability. However, such advantages may also limit political renewal, highlighting the need for institutional designs that balance accountability with electoral competitiveness.